2010
DOI: 10.1021/je100659q
|View full text |Cite
|
Sign up to set email alerts
|

Enthalpy of Solvation of Monoglyme, Diglyme, Triglyme, Tetraglyme, and Pentaglyme in Mixtures of Water with N,N-Dimethylformamide at 298.15 K

Abstract: The standard molar enthalpies of solution of linear polyethers (LPs) such as 1,2-dimethoxyethane (monoglyme), diethyleneglycol dimethyl ether (diglyme), triethyleneglycol dimethyl ether (triglyme), tetraethyleneglycol dimethyl ether (tetraglyme), and pentaethyleneglycol dimethyl ether (pentaglyme) in a mixture of water and N,N-dimethylformamide were measured at a temperature of 298.15 K. The values of standard molar enthalpy of solution, Δsol H m o, the enthalpic effect of hydrophobic hydration, Hb(H2O), and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 30 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…Lipophilicity is one the most important factors that has influence on a drugs' biological activity. 28 The complex 2 has the highest log P value (À1,82) and exhibits the highest cytotoxicity among the investigated complexes. However, the another important factor is the stability of compound.…”
Section: Cytotoxicity Studiesmentioning
confidence: 92%
“…Lipophilicity is one the most important factors that has influence on a drugs' biological activity. 28 The complex 2 has the highest log P value (À1,82) and exhibits the highest cytotoxicity among the investigated complexes. However, the another important factor is the stability of compound.…”
Section: Cytotoxicity Studiesmentioning
confidence: 92%
“…This is different from the conventional Li-ion (Na-ion) concept, where the solvent does not influence the cell voltage; see, e.g., ref . A series of glymes (mono-, di-, tri-, and tetraglyme, abbreviated as 1G, 2G, 3G, and 4G, respectively) have been tested in the meanwhile by several groups. Long cycle life and high currents can be generally achieved. For example, Cohn et al reported 8000 cycles at 12 A g –1 with 96% capacity retention when using 2G as the solvent .…”
Section: Introductionmentioning
confidence: 98%
“…The number of oxyethylene groups ( n ) in a glyme molecule determines its polarity. With an increase in the number of the –OCH 2 CH 2 – groups, the hydrophobic nature of a linear polyether molecule increases [ 15 ]. Open chain polyethylene glycols have been found to be capable of forming complexes with different metal cations in organic solvents, in a similar manner to the macrocyclic polyethers [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%